Advancing water adaptation indicators by bridging global ambitions and local realities in the UAE–Belém Work Programme - Attoh, Emmanuel M. N. A. N.; Osei-Amponsah, Charity; Akpoti, Komlavi; Alegbeleye, Oluwadara; Seidou, O.; Okem, A. E.; Adhiambo, P.; Kimanzi, M.; Denje, T.; Kung’u, F.; Naalamiley, C.; Awolala, D.; et al. (African Group of Negotiators Experts Support, 2025)
The escalating climate crisis demands a reimagining of how the world measures and achieves water-related adaptation, particularly in regions most vulnerable to hydrological extremes. The operationalization of the Global Goal on Adaptation (GGA) through the UAE–Belém Work Programme, marks a critical step toward systematizing global adaptation tracking. This opinion paper critiques the Programme’s progress as of June 2025, highlighting gaps in equity, data readiness, and contextual relevance. It underscores that the reliance on standardized, biophysical metrics risks is perpetuating the very inequalities it seeks to resolve. We argue that Africa’s emerging leadership in blending indigenous knowledge, community-driven innovation, and robust regional frameworks presents a transformative opportunity to reshape these indicators into tools of equity and resilience. The paper also provides actionable recommendations to align global ambitions with local realities, ensuring water adaptation indicators empower vulnerable communities and drive transformative resilience.